Ageing in a Gentrifying Neighbourhood: Experiences of Community Change in Later Life - Buffel, Tine; Phillipson, Chris (Sociology (Oxford), 2019)
Debates about gentrification continue to occupy a significant part of research investigating social change within urban communities. While most gentrification studies have focused on ‘incoming’ groups or those forced to leave, there is limited knowledge about those remaining in neighbourhoods undergoing community change. This study explores the experiences of older residents who have lived much of their adult lives in the same locality but whose views have been largely ignored in gentrification research. The article presents findings from seven focus groups (N = 58 participants) and 30 in-depth interviews with people aged 60 and over living in Chorlton, a gentrifying neighbourhood in Manchester, UK. These highlight both daily challenges and exclusionary pressures, as well as how people are active in creating a sense of belonging in a neighbourhood undergoing social change. The article concludes by discussing the need for interventions which promote the ‘age-friendliness’ of communities and ensure that older people have a space to be seen and heard in their neighbourhood.